Answer: The factorization of all the parts are :
Part A :
Part B :
Part C :
Step-by-step explanation: We are given to factorize the following quadratic polynomials :
Part A : Factor x²y² + 6xy² + 8y².
Part B : Factor x² + 8x + 16.
Part C: Factor x² − 16.
We will be using the following factorization formulas :
The factorization of all the parts area as follows :
Part A :
We have
So,
Part B :
We have
So,
Part C :
We have
So,
Thus, all the parts are factorized.
b. y = x + 3
c. x = y + 3
d. y = 3x
Is the statement true or false? (ab)c = a(cb).
a. True
b. False
Answer:
product y ³ - 64 and a = 16.
Step-by-step explanation:
Given : (y — 4)(y² + 4y + 16) .
To find : Using the distributive property to find the product a polynomial of the form y³ + 4y² + ay – 4y² – ay – 64. What is the value of a in the polynomial?
Solution : We have given
(y — 4)(y² + 4y + 16) .
Distribute y over (y² + 4y + 16) and - 4 over (y² + 4y + 16).
y (y² + 4y + 16) - 4 (y² + 4y + 16).
y ³+ 4y² + 16 y - 4y² - 16y - 64.
This is in form of y³ + 4y² + ay – 4y² – ay – 64.
Here, a = 16.
Product : combine like terms
y ³+ 4y² - 4y² + 16y - 16y - 64.
y ³ - 64.
Therefore , product y ³ - 64 and a = 16.
The average rate of change of f(x) over the interval -1 ≤ x ≤ 1 is -1.
Given the functionover the interval -1 ≤ x ≤ 1, we need to calculate the difference in the function values at the endpoints of the interval and divide it by the difference in the x-values.
The value of f(x) at the endpoint x = -1:
f(-1) = (-1)² - (-1) - 1 = 1 + 1 - 1 = 1
Now, the value of f(x) at the endpoint x = 1:
f(1) = (1)² - (1) - 1 = 1 - 1 - 1 = -1
The difference in the function values is:
f(1) - f(-1) = -1 - 1 = -2
The difference in the x-values is:
1 - (-1) = 2
Now, we can calculate the average rate of change:
Average rate of change = (f(1) - f(-1)) / (1 - (-1)) = -2 / 2 = -1
Therefore, the average rate of change of f(x) over the interval -1 ≤ x ≤ 1 is -1.
Learn more about average rate;
#SPJ12
Answer:
ff has an average rate of change of zero over the interval
−
1
≤
�
≤
2
−1≤x≤2minus, 1, is less than or equal to, x, is less than or equal to, 2.
Step-by-step explanation:
-1≤x≤2
To find the volume of an object, divide its mass by its density.
The volume of an object can be found by dividing its mass by its density. In this case, the mass is given as 63 grams and the density is given as 9 g/cm. To find the volume, divide the mass by the density: Volume = Mass / Density.
Substituting the given values, we get Volume = 63 g / 9 g/cm. Simplifying the equation, we find that the volume of the object is 7 cm³.
#SPJ2